The demosponge Halichondria (Halichondria) panicea (Pallas, 1766) as a novel source of biosurfactant‐producing bacteria. (23rd March 2018) - Rizzo, Carmen; Syldatk, Christoph; Hausmann, Rudolf; Gerçe, Berna; Longo, Caterina; Papale, Maria; Conte, Antonella; De Domenico, Emilio; Michaud, Luigi; Lo Giudice, Angelina
Abstract : The Mediterranean sponge Halichondria ( Halichondria ) panicea was explored as a novel matrix for the isolation of biosurfactant‐producing bacteria. A total of 38 (out of 56) isolates gave a good response to the employed screening tests (e.g., stable emulsion detection, surface tension measurement, hemolytic activity, and blue agar plate assay) and were selected for further analyses. The thin layer chromatography revealed a possible glucidic composition of biosurfactants. Most promising strains, i.e., those able to produce stable emulsion with percentage higher than 30% and yellow spots on TLC plates, were affiliated to the genera Pseudovibrio, Acinetobacter, and Bacillus . The biosurfactant production by two isolates (i.e., Acinetobacter sp. SpN134 and Pseudovibrio sp. SpE85) was evaluated under different culture conditions, in terms of temperature, NaCl concentration, and pH. Surface tension reduction ability was more stable than the emulsification, and resulted differently influenced by salinity, temperature, and pH. Acinetobacter sp. SpN134 resulted particularly efficient and competitive if compared with other well‐known biosurfactant producers. Data suggest that sponges may represent a promising matrix for the isolation of biosurfactant‐producing bacteria, reinforcing the growing interest towards filter‐feeding organisms as underexplored sources of specialized bacteria.